Severity analysis of fruit plant diseases based on leaf symptoms using ImageJ software - An Nissa Falaq Qurrahmah; Umi Mutfidasari; Putri Inayah Aisyah; Irene Putri Pricillia Butar-Butar; Imam Rosadi; Linda Oktavianingsih (Bioma : Jurnal Ilmiah Biologi, 2022)
Diseases in plants are abnormal and detrimental physiological processes plants. Plant organs commonly affected by the disease are leaves, roots, fruit, and stems. Diseases in plants can generally be caused by bacteria, fungi, viruses, and algae that cause diplodia, red rust patches/spots, scabies, and downy mildew. This study aims to determine the severity of disease in fruit plants using ImageJ and plantix. Based on the results of the study, found five types of fruit plants were used, namely grape vines (Vitis vinifera), sapodilla (Manilkara zapota), mango (Mangifera indica), rambutan (Nephelium sp.), and lime plants (Citrus aurantifolia) with different severity of plant diseases. The highest severity of the disease was found in rambutan leaves (43.73%) caused by fungi, and the lowest severity was found in lime leaves (16.12%) caused by fungi.